2013
DOI: 10.1111/tpj.12240
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis FRS4/CPD25 and FHY3/CPD45 work cooperatively to promote the expression of the chloroplast division gene ARC5 and chloroplast division

Abstract: SUMMARYARC5 is a dynamin-related GTPase essential for the division of chloroplasts in plants. The arc5 mutant frequently exhibits enlarged, dumbbell-shaped chloroplasts, indicating a role for ARC5 in the constriction of the chloroplast division site. In a screen for chloroplast division mutants with a phenotype similar to arc5, two mutants, cpd25 and cpd45, were obtained. CPD45 was identified as being the same gene as FHY3, a key regulator of far-red light signaling recently shown to be involved in the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 43 publications
(85 reference statements)
0
39
0
Order By: Relevance
“…In addition, several other proteins were reported to affect chloroplast division, but most of them showed no direct interactions with the chloroplast division machinery or the mechanisms of regulation were not clear (Basak and Møller, 2013). FHY3, a key regulator of far-red light signaling, and its homolog FRS4 were recently reported to bind the promoter region of DRP5B and activate its expression (Ouyang et al, 2011;Gao et al, 2013). These results showed that transcription factors are also involved in the regulation of chloroplast division, although a relationship between far-red light signaling and chloroplast division was not demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several other proteins were reported to affect chloroplast division, but most of them showed no direct interactions with the chloroplast division machinery or the mechanisms of regulation were not clear (Basak and Møller, 2013). FHY3, a key regulator of far-red light signaling, and its homolog FRS4 were recently reported to bind the promoter region of DRP5B and activate its expression (Ouyang et al, 2011;Gao et al, 2013). These results showed that transcription factors are also involved in the regulation of chloroplast division, although a relationship between far-red light signaling and chloroplast division was not demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…A mutant screen in Arabidopsis identified the transcription factor FHY3/CPD45, a key regulator of farred light signaling, and its homolog FRS4/CPD25, as coactivators of ARC5 (DRP5B) expression and chloroplast division (Gao et al, 2013). fhy3/cpd45 and frs4/cpd25 mutants had enlarged dumbbell-shaped chloroplasts, similar to arc5 (Fig.…”
Section: Regulation Of Chloroplast Divisionmentioning
confidence: 99%
“…DRP 5B, DRP5B/ARC5 (accumulation and replication of chloroplasts 5) is a functional GTPase, essential for the division of chloroplasts in plants and localized at the outer envelope of chloroplasts. DRP5B/ARC5 has two functional isoforms and plastid division proteins 1 and 2 (PDV1 and PDV2) interact with DRP5B/ARC5 and regulate its GTPase activity (Gao et al, 2013; Holtsmark et al, 2013). …”
Section: Experimentally Identified Molecular Components Of Chloroplasmentioning
confidence: 99%